PERENCANAAN STRUKTUR BAJA PADA BANGUNAN RUMAH SAKIT IBU DAN ANAK DI KABUPATEN TEGAL - Saputra, Wisnu; Kamal, Sukron; Kristiawan, Agung; Budirahardjo, Slamet (Universitas PGRI Semarang, 2023)
This thesis is planned in accordance with the regulations that apply to buildings including the Building and Structural Design Grading Regulations (SNI – 1727 -2013) Development Planning Guidelines for Houses and Buildings (PPPURG 1987) Procedures for Planning Steel Structures for Buildings (SNI-03) 1729-2015) Procedures for Planning Earthquake Resistance for Buildings (SNI 03 – 1726 – 2012) Procedures for calculating concrete structures for buildings (SNI 03-2847-2013). In this planning data analysis uses manual calculations assisted by excel and SAP 2000 v.14 programs and steel design calculations using the LRFD method. This plan uses a concrete roof plate with a thickness of 10 cm and a floor plate with a thickness of 12 cm. Calculation of columns and beams using SAP 2000 v.14 obtained column dimensions K1 = 350x350 K2 = 300x300 K3 = 250x250 and for BI = 350x175 and B2 = 300x150. In this plan, the foundation used is a mini pile foundation with a circular shape with a diameter of 40 cm, a depth of subgrade 7.2 m with a pile length of 6 m.Keywords: building regulations, SAP 2000 v.14